2016
DOI: 10.4172/pharmaceutical-sciences.1000191
|View full text |Cite
|
Sign up to set email alerts
|

Rationality of Antibiotic Usage in Pediatrics in Bengkulu, Indonesia: Gyssens? Criteria and Type of Therapy Analysis

Abstract: Infectious diseases are one of the biggest health problems not only in Indonesia, but also in the whole world. Prescribing antibiotics in Indonesia are quite high and increased the incidence of resistance. This study is aimed to evaluate the rationality of antibiotic use in children at the hospital qualitatively. This research is descriptive analysis of retrospective antibiotic prescribing data in children use a Gyssens' criteria and types of antibiotic therapy. Incidence of infection in children under 12 y of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 12 publications
1
4
1
2
Order By: Relevance
“…This study showed that the increase of children age of the incidence of typhoid fever was reduced. This was in line with previous research findings that the rate of infection in children decreased on age [7].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This study showed that the increase of children age of the incidence of typhoid fever was reduced. This was in line with previous research findings that the rate of infection in children decreased on age [7].…”
Section: Discussionsupporting
confidence: 93%
“…The results obtained in the study were high category which compared with previous studies obtaining the results that the use of antibiotics for Bengkulu hospital 0.6% belonging to not exactly dose [7].…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations